Adherence to infection prevention measures in a statewide spleen registry. Issue 9 (19th May 2014) - Wang, Julie; Jones, Penelope; Cheng, Allen C; Leder, Karin
Abstract: Objective: To assess self‐reported adherence to measures for preventing infection in patients registered in the Victorian Spleen Registry (VSR). Design, participants and setting: Cross‐sectional survey in May 2010 of all patients who had been registered on the VSR for at least 5 months, were able to speak English, and were not living in an institution. Main outcome measures: Rates of prophylactic antibiotic use, having an emergency supply of antibiotics available, receipt of any recommended booster vaccination (in patients at > 5 years since splenectomy) and receipt of 2009 influenza vaccination. Results: 1175 patients were sent questionnaires, of whom 889 (75.7%) responded. Self‐reported adherence to taking prophylactic antibiotics was lower with time since splenectomy (82.9% for < 2 years since splenectomy, 27.4% for ≥ 30 years), as was having an emergency supply of antibiotics available (74.4% for < 2 years and 60% for ≥ 30 years since splenectomy). The proportion receiving the seasonal influenza vaccine and recent booster vaccines (for those at > 5 years since splenectomy) was high. Of patients registered for more than 12 months, 37.0% reported an infection requiring additional antibiotics within the prior year, and 26.1% of these required hospitalisation (including one with a case of overwhelming postsplenectomy infection [OPSI]). Use of prophylactic antibiotics was inversely associated with the rate of infections requiring additional antibiotic therapy (odds ratio, 0.75; 95% CI, 0.57–0.98; P = 0.036). Conclusions: The proportion of VSR registrants adhering to current postsplenectomy guidelines was higher than rates reported elsewhere, and over a third reported infections requiring a course of antibiotics within the prior 12 months. However, only one OPSI occurred. These results support the view that a spleen registry can promote health maintenance behaviour in asplenic patients, which is likely to help prevent serious infections.